DO ISLAMIC EQUITY STYLE INDICES CONTAIN ECONOMIC INFORMATION? - Shahrin Saaid Shaharuddin; Wee-Yeap Lau; Tien-Ming Yip (Journal of Islamic Monetary Economics and Finance, 2020)
This study aims to investigate whether the Islamic equity style index contains economic information which is useful for investors and financial practitioners. The study fills the gap in the previous literature by investigating the relationship between Islamic equity style indices and macroeconomic variables. Using a Vector Autoregressive (VAR) model with monthly data from June 2006 to May 2017, our results show that first, there is unidirectional flow of information from Large Growth (LG) to the Leading Economic Indicator (LEI); second, Large Growth (LG) Granger-causes the Kuala Lumpur Composite Index (KLCI); third, Large Value (LV) also Granger-causes KLCI. A robustness check with an Augmented VAR model obtained similar results to the short-run model. Our results imply that equity style indices have prior information which is faster than LEI and KLCI. This knowledge is certainly useful for fund managers when designing Shariah-compliant portfolio investments. For policymakers, Islamic equity style indices are useful for predicting the direction of other macroeconomic variables such as business cycles, and hence help to predict the future direction and turning points in the economy.